Analysis of Students Perceptions of the Utility of Google Translate in Assisting Comprehension of English Texts at Muhammadiyah 3 Jember - Mohammad Slamet Hamdani; Henri Fatkurochman; Muhlisin Rasuki (Institut Agama Islam Tarbiyatut Tholabah, 2026)
This study examines students’ perceptions of Google Translate in assisting English texts comprehension at Muhammadiyah 3 Jember Senior High School, in Indonesia. The study had two focuses namely evaluating the benefits and limitations of GT as a learning tool. Using a descriptive quantitative method, data was collected through a Likert scale questionnaire to eleventh-grade students and analyzed using SPSS 27. The results showed that 91.4% of students viewed GT positively due to its accessibility, time efficiency, and practicality compared to traditional dictionaries. Key benefits included vocabulary enrichment, assistance in understanding word and sentence meaning, and better pronunciation through audio features. However, there were some limitations that emerged: 25.9% doubted the accuracy of paragraph levels, 80.2% acknowledging the risk of changing the meaning of the text, 69.2% criticized the unorganized sentence structure, and 30.8% expressed concerns about over-reliance hindering critical thinking. The study concludes that while GT effectively support comprehension, teacher-guided translation verification is important to reduce inaccuracies and dependency. This research contributes to technology-enhanced language learning by advocating a balanced and wise use of translation tools. Future research is recommended using mixed methods and a wider range of educational contexts.